PENGARUH KREDIT MODAL KERJA TERHADAP PROFIT NASABAH (Studi Pada Nasabah UMKM PD. BPR NTB Sumbawa) - U Usman; Deka Ayulia Saputri (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of working capital credit (KMK) on increasing profits for micro, small and medium enterprise customers (UMKM) in PD. BPR NTB Sumbawa. This research is a causal associative research conducted to examine the effect of working capital loans (KMK) on increasing the profit of UMKM customers in PD. BPR NTB Sumbawa. The type of data used is quantitative data in the form of respondents' responses in answering questionnaire questions distributed to research respondents. The population in this study are all UMKM customers at PD. BPR NTB Sumbawa totaling 212 people. The sample was taken using the Slovin formula with a margin of error of 10% so that the sample in this study was 68 people. The data that has been collected will then be processed using the SPSS program to be studied using techniques that include simple linear regression analysis, individual parameter hypothesis testing (t test), and determinant coefficient test (R2). The conclusion obtained from the results of this study is that working capital credit has a positive and significant effect on the profit of micro, small and medium enterprise customers (UMKM) in PD. BPR NTB Sumbawa. The degree of influence of working capital credit on the profit of micro, small and medium enterprise customers (UMKM) in PD. NTB Sumbawa is 85.8%, while the remaining 14.2% is influenced by other variables outside this research model, such as business experience, workforce, level of education, business partnerships, technology, marketing outreach, and others.